Karst grouting material and preparation method thereof
By combining modified electrolytic manganese slag, chlor-alkali industrial waste slag and cement clinker, combined with mechanical and thermally activated slag micro powder, karst grouting materials with high strength and moderate flow, the performance of existing grouting materials and The problem of insufficient safety has achieved environmentally friendly and efficient karst treatment.
Patent Information
- Application Number
- CN202411324637.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-20
AI Technical Summary
Existing karst grouting materials have shortcomings in performance, safety and environmental protection, especially the problems of poor interface adhesion, long settling time, expensive or undetermined safety.
Compound excitants are prepared in a ratio of 25:3:4 by modified electrolytic manganese slag, chlor-alkali industrial waste slag and cement clinker, combined with modified slag micro powders treated with mechanical activation and thermal activation, and added polycarboxylic acid water reducing agent to prepare strength Karst grouting material with high flow, moderate settling time.
It has achieved karst grouting materials with high strength, moderate flow and anti-seepage properties, and the preparation process is simple, it can effectively treat industrial solid waste, save energy, and exhibit good stability and low pollution characteristics in environmental safety. .
Smart Images

Figure CN119161146A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of civil engineering, and in particular relates to a karst grouting material and a preparation method thereof. Background Art
[0002] Electrolytic manganese slag is an industrial solid waste produced during the production of electrolytic manganese, when manganese ore is treated by sulfuric acid leaching and other processing methods. China is the world's largest producer of electrolytic manganese, with an annual output of more than 1.5 million tons and a cumulative output of 150 million tons. At present, the utilization rate of electrolytic manganese slag produced in the production process of electrolytic manganese is very low. A large amount of electrolytic manganese slag is piled up in landfills without any treatment. The manganese-related industry is most concentrated in China's "Manganese Triangle" region. China's "Manganese Triangle" region is a karst landform with relatively developed karst. The concentrations of sulfate, ammonia nitrogen and manganese in electrolytic manganese slag are extremely high, and heavy metals such as arsenic, nickel, and lead and small particulate matter can easily enter groundwater and soil, posing great environmental risks. Therefore, using electrolytic manganese slag as the basic material for karst grouting and yard plugging can effectively solve the yard leakage problem caused by manganese slag storage and karst development.
[0003] The main chemical components of electrolytic manganese slag are CaSO4·2H2O, SiO2 and a small amount of Al2O3, Fe2O3, MnO2, etc. It has the properties of gypsum and water industrial solid waste. Due to the low activity of CaSO4·2H2O and the acidic environment, the direct use of electrolytic manganese slag will inevitably reduce the performance of cement-based materials and cause performance changes. Existing literature confirms that the application of electrolytic manganese slag in building materials has a significant negative effect, which has a negative impact on the mechanical properties and microstructure of cementitious materials to varying degrees, and must be activated before it can be used. In view of the harmless treatment and high sulfate content of electrolytic manganese slag, incorporating electrolytic manganese slag into cement-based materials as a partial substitute for cement is one of the more ecologically beneficial methods, and is often used to prepare Portland cement and sulphoaluminate cement.
[0004] Calcination is one of the commonly used solid waste pretreatment methods. Calcination of electrolytic manganese slag has been proven to not only remove harmful substances in electrolytic manganese slag, but also improve the reaction activity of electrolytic manganese slag. Calcinated electrolytic manganese slag has been used to prepare soil remediation agents, non-sintered permeable bricks, etc., and has achieved good results. However, medium and high temperature calcination consumes a lot of energy and is not in line with the concept of low-carbon production. Studies have found that low-temperature calcination converts dihydrate gypsum in electrolytic manganese slag into hemihydrate gypsum, which has a higher solubility in an alkaline environment, effectively improving the reactivity of electrolytic manganese slag, and for the polluting ions present in the electrolytic manganese slag, although low-temperature calcination cannot completely remove Mn in the electrolytic manganese slag. 2+ and NH4 +-N, but can be completely stabilized. Slag is a glassy mineral composed of a three-dimensional structure formed by active CaO, SiO2 and Al2O3. From the chemical composition point of view, blast furnace slag belongs to silicate material, an amorphous glass, with potential volcanic ash activity, which requires external stimulation to stimulate its activity.
[0005] At present, the commonly used grouting materials are mainly composed of traditional cement-water glass, chemical polymers, microbial induced carbonate precipitation (MICP), etc. Cement-water glass double cement slurry is the most commonly used cement slurry in dynamic water-stopping projects, but its poor interfacial adhesion and long setting time affect its application and plugging efficiency, and the large-scale use of water glass has the risk of groundwater pollution. Although chemical grouting has high early strength and good grouting properties, it is expensive and may pollute the environment. MICP is a new grouting technology that has emerged in the past 20 years. It uses bacteria to deposit calcium carbonate through metabolic activities to plug or repair soil cracks. MICP technology has the advantages of simple construction conditions, low energy consumption, high repair strength, and low permeability, but its safety and reliability are still uncertain. For example, the durability of MICP-treated materials has not been confirmed, and the urea decomposition process is prone to produce high concentrations of NH4 + and NH3 (incomplete reaction) may harm the environment and human health.
[0006] Therefore, it is urgent to develop a karst grouting material with low price, good performance and high safety. Summary of the invention
[0007] The object of the present invention is to provide a karst grouting material and a preparation method thereof. The karst grouting material prepared by the present invention has high strength, large fluidity, moderate setting time, good impermeability, good effect of solidifying manganese and ammonia nitrogen, and simple preparation process.
[0008] In order to achieve the above purpose, this application adopts the following technical solutions:
[0009] In the first aspect, the present invention provides a karst grouting material, which is made of the following raw materials in parts by weight: 10-50 parts of a composite activator, 20-70 parts of modified slag powder, 30 parts of cement clinker, 60-100 parts of water, and 1 part of a polycarboxylic acid water reducer; wherein the composite activator is a mixture of modified electrolytic manganese slag, chlor-alkali industrial waste residue and cement clinker, and the weight ratio of each component is 25:3:4.
[0010] In the above technical solution, the modified electrolytic manganese slag is prepared by drying the electrolytic manganese slag and then subjecting it to mechanical activation modification and thermal activation modification.
[0011] In the above technical solution, the mechanical activation modification is performed by grinding using a planetary ball mill.
[0012] In the above technical solution, the thermal activation modification is to thermally activate and calcine the electrolytic manganese slag after mechanical activation modification at 190-400° C., and then cool it to room temperature.
[0013] In the above technical solution, the median particle size d of the modified electrolytic manganese slag is 50 The specific surface area is ≤7.961μm and ≥1.52m 2 / g; the cement clinker is P.O42.5 ordinary Portland cement clinker, with a median particle size of 27.812μm and a specific surface area of 0.797m 2 / g; the content of calcium oxide in the chlor-alkali industrial waste residue is 63.8%.
[0014] In the above technical solution, the modified slag powder is a material obtained by surface activation of slag. The slag is S95 grade, with a median particle size d 50 ≤11.549μm, specific surface area ≥1.42m 2 / g. The slag surface activation is carried out by using an alkaline solution, the pH of the treatment solution is 10-14, the treatment time is 30-60 minutes, and the treatment temperature is 60-80°C.
[0015] In a second aspect, the present invention provides a method for preparing a karst grouting material, comprising the following steps:
[0016] S1. preparing modified electrolytic manganese slag: drying the electrolytic manganese slag, and then subjecting the electrolytic manganese slag to mechanical activation modification and thermal activation modification to obtain the modified electrolytic manganese slag;
[0017] S2. Prepare the composite activator: prepare the modified electrolytic manganese slag: chlor-alkali industrial waste slag: cement clinker in a weight ratio of 25:3:4;
[0018] S3, add 1 part of polycarboxylate water reducer to 60-100 parts of water, stir evenly and pour into a mixer;
[0019] S4. Pour 20-70 parts of modified slag powder and 30 parts of cement clinker into a mixer and mix them evenly. Stir at a low speed for 2 minutes, stop for 30 seconds, use a scraper to scrape the slurry from the blades, pot wall and pot bottom into the pot, and continue stirring at a high speed for 60 seconds. Finally, pour in 10-50 parts of the composite excitation and repeat the above stirring work to obtain the karst grouting material.
[0020] The beneficial effects of the present invention are:
[0021] 1. The present invention uses electrolytic manganese slag, blast furnace slag and chlor-alkali industrial waste residue as main raw materials to prepare karst grouting materials, which can effectively treat industrial solid waste and open up an effective way for the comprehensive utilization of industrial waste residues.
[0022] 2. Compared with high-temperature calcination, medium- and low-temperature calcination of electrolytic manganese slag can save more energy consumed by EMR modification.
[0023] 3. The present invention uses slag to replace Portland cement to improve the fluidity of cement slurry and increase the setting time. The sulfate contained in the electrolytic manganese slag provides the required sulfate concentration for the successful activation of the slag.
[0024] 4. Modified slag powder effectively improves the dispersibility of slag powder and enhances its bonding with the matrix material, thereby improving the mechanical properties and environmental stability of the overall material.
[0025] 5. The karst grouting material prepared in the present invention has high strength, large fluidity, moderate setting time, good impermeability, good effect of solidifying manganese and ammonia nitrogen, and simple preparation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a preparation flow chart of the karst grouting material of the present invention;
[0027] Figure 2 This is a microscopic morphology of a 28d hardened sample of the manganese slag-based high-efficiency grouting material prepared in Example 1 of the present invention;
[0028] Figure 3 This is a microscopic morphology of a 28d hardened sample of a manganese slag-based high-efficiency grouting material prepared in Example 2 of the present invention;
[0029] Figure 4 This is a microscopic morphology of a 28d hardened sample of a manganese slag-based high-efficiency grouting material prepared in Example 3 of the present invention;
[0030] Figure 5 This is a microscopic morphology of a 28d hardened sample of a manganese slag-based high-efficiency grouting material prepared in Example 4 of the present invention;
[0031] Figure 6 This is a microscopic morphology of a 28d hardened sample of the manganese slag-based high-efficiency grouting material prepared in Example 5 of the present invention. DETAILED DESCRIPTION
[0032] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. The present invention can be implemented in many different forms and should not be construed as being limited to the embodiments set forth herein. On the contrary, these embodiments are provided so that this disclosure will be thorough and complete, and the concept of the present invention will be fully conveyed to those skilled in the art, and the present invention will only be limited by the claims.
[0033] The raw materials used in the following embodiments of the present invention are:
[0034] The electrolytic manganese slag is obtained from the Tongren manganese mine in Guizhou, and then undergoes a modification process to obtain the modified electrolytic manganese slag. The specific modification process is: the electrolytic manganese slag is dried at 80°C, and then mechanically activated and thermally activated. The mechanical activation modification is grinding with a planetary ball mill, and the thermal activation modification is thermally activated calcining of the electrolytic manganese slag after mechanical activation modification at 190-400°C, and then cooled to room temperature for standby use. The median particle size d of the modified electrolytic manganese slag is 50 The specific surface area is ≤7.961μm and ≥1.52m 2 / g.
[0035] The slag was obtained from Lingshou Yiteng New Material Technology Co., Ltd. and crushed into slag powder. The blast furnace slag powder was S95 grade with a median particle size of d 50 ≤11.549μm, specific surface area ≥1.42m 2 / g. The slag powder needs to be modified to obtain the modified slag powder. The specific modification process is: using an alkaline solution (such as NaOH solution) of a specific concentration (pH = 10-14) for surface activation treatment for 30-60 minutes at a temperature of 60-80°C. This step helps to expose more active sites.
[0036] The chlor-alkali industrial waste residue was obtained from Henan Wardmei Environmental Protection Technology Co., Ltd. The content of calcium hydroxide in the chlor-alkali industrial waste residue was 63.8%.
[0037] Cement clinker was obtained from Wuxi Jianghuai Building Materials Technology Co., Ltd. Cement used was 42.5 ordinary Portland cement (P·O 42.5). The cement clinker was P.O42.5 ordinary Portland cement clinker with a median particle size of 27.812 μm and a specific surface area of 0.797 m 2 / g.
[0038] The composite activator is prepared from modified electrolytic manganese slag / chlor-alkali industrial waste slag / cement clinker in a mass ratio of 25:4:3.
[0039] The polycarboxylate water reducer was obtained from Sichuan Dongrun Baisheng New Materials Co., Ltd. and is a standard polycarboxylate water reducer.
[0040] The chemical composition of each raw material is shown in Table 1 below.
[0041] Table 1 Chemical composition of modified electrolytic manganese slag, modified slag powder, cement clinker, and chlor-alkali industrial waste slag (wt.%)
[0042]
[0043]
[0044] According to L16(4 4) orthogonal table (see Table 2) The modified electrolytic manganese slag, chlor-alkali industrial waste slag and cement clinker at different temperatures were compounded to prepare the composite activator. Then the composite activator and the modified slag powder were added to the modified slag powder in a weight ratio of 3:7 to produce blast furnace slag powder modified by electrolytic manganese slag. Finally, the 3d activity index (A3), 7d activity index (A7) and 28d activity index (A28) of the modified activator were measured to evaluate the activating effect of the composite activator on blast furnace slag and determine the optimal manganese-based composite activator ratio. As shown in Table 2, the results of A3, A7 and A28 show that the optimal composite activator addition ratio is: modified electrolytic manganese slag / chlor-alkali industrial waste slag / cement clinker at 300 degrees Celsius = 25:3:4.
[0045] Then, the setting time, fluidity, compressive strength and flexural strength of the karst grouting material prepared by mixing modified slag micropowder and cement clinker with composite activator are measured, and finally the addition proportion and water-cement ratio of the grouting material additives suitable for various engineering environments are determined.
[0046] Table 2 Orthogonal test of compound activator ratio of electrolytic manganese slag
[0047]
[0048] Embodiment 1:
[0049] Raw materials used in the preparation of karst grouting materials: 25 parts of composite activator, 45 parts of modified slag powder, 30 parts of cement clinker, 60 parts of water, and 1 part of polycarboxylic acid water reducer. The composite activator is prepared from modified electrolytic manganese slag / chlor-alkali industrial waste slag / cement clinker in a mass ratio of 25:4:3.
[0050] The preparation method of the grouting material comprises the following steps:
[0051] S1. Prepare mixed powder 1 with 45 parts of modified slag powder and 30 parts of cement clinker;
[0052] S2, uniformly mixing 25 parts of the composite activator according to the proportion to prepare mixed powder 2;
[0053] S3, add 1 part of polycarboxylate water reducer to 60 parts of water, stir evenly and introduce into the pot of mixer for standby use;
[0054] S4. Put the mixed powder 1 into the blender and stir it at a low speed for 2 minutes, stop for 30 seconds, scrape the slurry from the blades, pot wall and pot bottom into the pot with a scraper, and continue stirring at a high speed for 60 seconds. Then pour the mixed powder 2 into the pot and stir it at a low speed for 2 minutes, stop for 30 seconds, scrape the slurry from the blades, pot wall and pot bottom into the pot with a scraper, and continue stirring at a high speed for 60 seconds to obtain the grouting material for karst plugging in the manganese ore reservoir area.
[0055] Embodiment 2:
[0056] Raw materials used in the preparation of karst grouting materials: 25 parts of composite activator, 45 parts of modified slag powder, 30 parts of cement clinker, 80 parts of water, and 1 part of polycarboxylic acid water reducer. The composite activator is prepared from modified electrolytic manganese slag / chlor-alkali industrial waste slag / cement clinker in a mass ratio of 25:4:3.
[0057] The preparation method of the grouting material comprises the following steps:
[0058] S1. Prepare mixed powder 1 with 45 parts of modified slag powder and 30 parts of cement clinker;
[0059] S2, uniformly mixing 25 parts of the composite activator according to the proportion to prepare mixed powder 2;
[0060] S3, add 1.5 parts of polycarboxylate water reducer to 80 parts of water, stir evenly and introduce into the pot of the mixer for standby use;
[0061] S4. Put the mixed powder 1 into the blender and stir it at a low speed for 2 minutes, stop for 30 seconds, scrape the slurry from the blades, pot wall and pot bottom into the pot with a scraper, and continue stirring at a high speed for 60 seconds. Then pour the mixed powder 2 into the pot and stir it at a low speed for 2 minutes, stop for 30 seconds, scrape the slurry from the blades, pot wall and pot bottom into the pot with a scraper, and continue stirring at a high speed for 60 seconds to obtain the grouting material for karst plugging in the manganese ore reservoir area.
[0062] Example 3
[0063] Raw materials used in the preparation of karst grouting materials: 25 parts of composite activator, 45 parts of modified slag powder, 30 parts of cement clinker, 100 parts of water, and 1 part of polycarboxylic acid water reducer. The composite activator is prepared from modified electrolytic manganese slag / chlor-alkali industrial waste slag / cement clinker in a mass ratio of 25:4:3.
[0064] The preparation method of the grouting material comprises the following steps:
[0065] S1. Prepare mixed powder 1 with 45 parts of modified slag powder and 30 parts of cement clinker;
[0066] S2, uniformly mixing 25 parts of the composite activator according to the proportion to prepare mixed powder 2;
[0067] S3, add 1 part of polycarboxylate water reducer to 100 parts of water, stir evenly and introduce into the pot of the mixer for standby use;
[0068] S4. Put the mixed powder 1 into the blender and stir it at a low speed for 2 minutes, stop for 30 seconds, scrape the slurry from the blades, pot wall and pot bottom into the pot with a scraper, and continue stirring at a high speed for 60 seconds. Then pour the mixed powder 2 into the pot and stir it at a low speed for 2 minutes, stop for 30 seconds, scrape the slurry from the blades, pot wall and pot bottom into the pot with a scraper, and continue stirring at a high speed for 60 seconds to obtain the grouting material for karst plugging in the manganese ore reservoir area.
[0069] Example 4
[0070] Raw materials used in the preparation of karst grouting materials: 10 parts of composite activator, 60 parts of modified slag powder, 30 parts of cement clinker, 80 parts of water, and 1 part of polycarboxylic acid water reducer. The composite activator is prepared from modified electrolytic manganese slag / chlor-alkali industrial waste slag / cement clinker in a mass ratio of 25:4:3.
[0071] The preparation method of the grouting material comprises the following steps:
[0072] S1. Prepare mixed powder 1 by 70 parts of modified slag powder and 30 parts of cement clinker;
[0073] S2, uniformly mixing 25 parts of the composite activator according to the proportion to prepare mixed powder 2;
[0074] S3, add 0.5 parts of polycarboxylate water reducer to 80 parts of water, stir evenly and introduce into the pot of the mixer for standby use;
[0075] S4. Put the mixed powder 1 into the blender and stir it at a low speed for 2 minutes, stop for 30 seconds, scrape the slurry from the blades, pot wall and pot bottom into the pot with a scraper, and continue stirring at a high speed for 60 seconds. Then pour the mixed powder 2 into the pot and stir it at a low speed for 2 minutes, stop for 30 seconds, scrape the slurry from the blades, pot wall and pot bottom into the pot with a scraper, and continue stirring at a high speed for 60 seconds to obtain the grouting material for karst plugging in the manganese ore reservoir area.
[0076] Example 5
[0077] Raw materials used in the preparation of karst grouting materials: 50 parts of composite activator, 20 parts of modified slag powder, 30 parts of cement clinker, 80 parts of water, and 1 part of polycarboxylic acid water reducer. The composite activator is prepared from modified electrolytic manganese slag / chlor-alkali industrial waste slag / cement clinker in a mass ratio of 25:4:3.
[0078] The preparation method of the grouting material comprises the following steps:
[0079] S1. Prepare mixed powder 1 by 20 parts of modified slag powder and 30 parts of cement clinker;
[0080] S2, uniformly mix 50 parts of the composite activator according to the proportion to prepare mixed powder 2;
[0081] S3, add 1 part of polycarboxylate water reducer to 80 parts of water, stir evenly and introduce into the pot of the mixer for standby use;
[0082] S4. Put the mixed powder 1 into the blender and stir it at a low speed for 2 minutes, stop for 30 seconds, scrape the slurry from the blades, pot wall and pot bottom into the pot with a scraper, and continue stirring at a high speed for 60 seconds. Then pour the mixed powder 2 into the pot and stir it at a low speed for 2 minutes, stop for 30 seconds, scrape the slurry from the blades, pot wall and pot bottom into the pot with a scraper, and continue stirring at a high speed for 60 seconds to obtain the grouting material for karst plugging in the manganese ore reservoir area.
[0083] Experimental Procedure
[0084] The grouting material slurry obtained in Examples 1-5 was poured into a triple test mold with a size of 40mm×40mm×160mm to cast the specimens. The cast specimens were demolded after being cured for 24 hours under standard curing conditions (temperature 20±2°C, relative humidity ≥95%). After demolding, they were continued to be cured under standard curing conditions until the test age.
[0085] The compressive strength and flexural strength of cement mortar were measured according to GB / T 17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)". The setting time was tested according to GB / T 1346-2011 "Test Method for Water Consumption, Setting Time and Stability of Cement Standard Consistency". In order to prevent the influence of pseudo-setting of hemihydrate gypsum on the setting time, it is necessary to ensure that the plasticity cannot be restored by re-stirring without adding additional water when judging the setting. With reference to GB / T2419-2005 "Measurement Method for Fluidity of Cement Mortar", the micro-slump test is defined as the spread diameter of the new grouting material on the plate. The slump has a bottom diameter of 36 mm, a top diameter of 60 mm and a height of 60 mm. The 28-day toxic leaching of the sample was tested with reference to the Chinese standard (HJ / T 299-2007). The size of the permeability test sample was 50*50 cylindrical, and the sample was saturated by the vacuum saturation method. The permeability coefficient of the saturated material was then measured using a flexible wall permeameter. The applied confining pressure was 80 kPa and the osmotic pressure was 60 kPa. For specific steps, see ASTM D5887M-22a and ASTM D5084-03. The permeate was deionized water.
[0086] The test results are shown in Table 3-5 below. The higher the water-cement ratio, the longer the slurry setting time. With the increase of the composite activator content, the initial setting time first increases and then decreases, and finally stabilizes. The fluidity decreases with the increase of the composite activator content and increases with the increase of the water-cement ratio. The strength first increases and then decreases with the increase of the composite activator and decreases with the increase of the water-cement ratio. The permeability coefficient first decreases and then increases with the increase of the composite activator.
[0087] Table 3 Setting time and fluidity of slurry
[0088] Example Initial setting time / min Final setting time / min Fluidity / mm 1 150 350 155 2 240 395 190 3 330 505 235 4 390 450 300 5 210 365 132
[0089] Table 4 Strength results
[0090]
[0091] Table 5 Permeability coefficient
[0092] Example 3d 7d 28d 1 <![CDATA[4.2542×10 -8 ]]> <![CDATA[1.185×10 -8 ]]> <![CDATA[9.3882×10 -9 ]]> 2 <![CDATA[8.7136×10 -8 ]]> <![CDATA[2.188×10 -8 ]]> <![CDATA[2.7991×10 -8 ]]> 3 <![CDATA[3.2552×10 -7 ]]> <![CDATA[1.2215×10 -7 ]]> <![CDATA[7.3982×10 -8 ]]> 4 <![CDATA[1.113×10 -7 ]]> <![CDATA[9.0279×10 -8 ]]> <![CDATA[6.8645×10 -8 ]]> 5 <![CDATA[2.1295×10 -7 ]]> <![CDATA[9.9398×10 -8 ]]> <![CDATA[7.477×10 -8 ]]>
[0093] In order to ensure the safety of grouting materials and avoid secondary pollution caused by leaching of contaminated ions, a 28-day toxicity leaching test must be carried out on the hardened grouting material. Dissolve the mixed solution of sulfuric acid and nitric acid in distilled water at a mass ratio of 2:1, and adjust the pH to 3.20±0.05. After the compression test, the sample is crushed and passed through a 9.5mm sieve. After the sample and the extract are mixed at a ratio of 1:10 (mL / g), they are placed in a flip oscillator with an oscillation frequency of 30±2r / min and oscillated at 23±2℃ for 18±2h. Subsequently, the extract is allowed to stand and then filtered through a 0.45mm filter membrane. The collected extract is stored at 4℃ for testing. Mn in the leachate 2+ and NH 4+ The concentrations of were tested according to Chinese standards (GB 11906-89 and HJ 535-2009). As shown in Table 6.
[0094] Table 6 Mn in leachate 2+ and NH 4+ The concentration results
[0095]
[0096] NH4 is barely detectable in toxic leach solutions + , indicating that NH4 + It has been completely fixed and will not produce NH3 to pollute the environment during engineering application. 2+ The grouting materials prepared in Examples 1-5 are effectively stabilized / solidified and will not leach heavy metal ions in engineering applications. The grouting materials prepared in Examples 1-5 have good environmental safety.
[0097] from Figure 2 It is concluded that the needle-shaped C-(A)-SH gel in the hardened body formed by the 28d hardening sample of the grouting material prepared in Example 1 undergoes a "agglomeration" phenomenon to form short rods and vermiculite, which can effectively fill the pores, and the material has a short setting time. The sample can be used for repairing and plugging leakage channels and for projects with high strength requirements; Figure 3 It can be concluded that the 28d hardened sample of the grouting material prepared in Example 2 has a relatively compact structure, a small pore structure, and excellent strength, and is suitable for projects that have certain requirements on fluidity and strength; Figure 4 It can be concluded that the 28d hardened sample of the grouting material prepared in Example 3 has a relatively loose structure, a large pore structure, and a relatively low strength, but a high fluidity, and can be used in engineering conditions with high fluidity requirements; Figure 5 It is concluded that the 28d hardening sample of the grouting material prepared in Example 4 has no composite activator added, and the main hydration product is a needle-shaped C-(A)-SH gel with a small amount of pores, which is suitable for engineering conditions with high fluidity requirements and not low strength; Figure 6 It was concluded that in the 28d hardened sample of the grouting material prepared in Example 5, the amount of calcium sulfonate gradually increased, and the excessive amount of needle-shaped calcium sulfonate filled the microstructure of the hardened body, thereby forming a large number of pore structures, resulting in reduced mechanical strength of the hardened body and low fluidity, but a fast setting time. It is suitable for emergency repair and plugging projects with low strength requirements.
[0098] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A karst grouting material, characterized in that: The invention is made of the following raw materials in parts by weight: 10-50 parts of a composite activator, 20-70 parts of modified slag powder, 30 parts of cement clinker, 60-100 parts of water and 1 part of a polycarboxylic acid water reducer; wherein the composite activator is a mixture of modified electrolytic manganese slag, chlor-alkali industrial waste residue and cement clinker, and the weight ratio of each component is 25:3:
4.
2. The karst grouting material according to claim 1, characterized in that: The modified electrolytic manganese slag is prepared by drying the electrolytic manganese slag and then subjecting it to mechanical activation modification and thermal activation modification.
3. The karst grouting material according to claim 2, characterized in that: The mechanical activation modification is performed by grinding using a planetary ball mill.
4. The karst grouting material according to claim 2, characterized in that: The thermal activation modification is to thermally activate and calcine the electrolytic manganese slag after mechanical activation modification at 190-400° C., and then cool it to room temperature.
5. The karst grouting material according to claim 1, characterized in that: The median particle size d of the modified electrolytic manganese slag 50 The specific surface area is ≤7.961μm and ≥1.52m 2 / g; the cement clinker is P.O42.5 ordinary Portland cement clinker, with a median particle size of 27.812μm and a specific surface area of 0.797m 2 / g; the content of calcium oxide in the chlor-alkali industrial waste residue is 63.8%.
6. The karst grouting material according to claim 1, characterized in that: The modified slag powder is a material obtained by surface-activating slag.
7. The karst grouting material according to claim 6, characterized in that: The slag is of S95 grade, with a median particle size of d 50 ≤11.549μm, specific surface area ≥1.42m 2 / g.
8. The karst grouting material according to claim 6, characterized in that: The slag surface activation adopts alkaline solution for surface activation treatment, the pH of the treatment solution is 10-14, the treatment time is 30-60 minutes, and the treatment temperature is 60-80°C.
9. A method for preparing a karst grouting material, characterized in that: The following steps are involved: S1. preparing modified electrolytic manganese slag: drying the electrolytic manganese slag, and then subjecting the electrolytic manganese slag to mechanical activation modification and thermal activation modification to obtain the modified electrolytic manganese slag; S2. Prepare the composite activator: prepare the modified electrolytic manganese slag: chlor-alkali industrial waste slag: cement clinker in a weight ratio of 25:3:4; S3, add 1 part of polycarboxylate water reducer to 60-100 parts of water, stir evenly and pour into a mixer; S4. Pour 20-70 parts of modified slag powder and 30 parts of cement clinker into a mixer and mix them evenly. Stir at a low speed for 2 minutes, stop for 30 seconds, use a scraper to scrape the slurry from the blades, pot wall and pot bottom into the pot, and continue stirring at a high speed for 60 seconds. Finally, pour in 10-50 parts of the composite activator and repeat the above stirring work to obtain the karst grouting material.
